Transparansi dan Akuntabilitas dalam Proses Legislasi: Studi Kasus Pembentukan Undang-Undang Menurut Pasal 1 Angka 1 UU Nomor 12 Tahun 2011 - Acumen Makmur; Ce Kedzma Alvian; Indok Siti Balqis; Jihan Hanifah; Nabil Musyafa; Tanti Kirana Utami (Cattleya Darmaya Fortuna, 2025)
The 1945 Constitution of the Republic of Indonesia, which contains legal norms that form the basis for operational foundations to realize the goals and ideals of the Indonesian rule of law, regulates the formation of the basis or principles for organizing the state. However, in practice, political compromise tends to be the main focus in pouring legal norms in the Constitution into laws. This is considered to have the potential to cause problems due to misunderstandings about the Indonesian justice system. This study uses a normative legal research method using legal materials as data sources. The research findings show that the formation of laws involves a multi-step process that includes phases such as preparation, drafting, discussion, ratification, and implementation. The process of forming laws that represent the goals of society while complying with relevant legal requirements can be understood and analyzed using the conceptual framework offered by the theory of legislation.